The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/s0103-84782013005000136
|View full text |Cite
|
Sign up to set email alerts
|

Compostos nitrogenados sobre o consumo alimentar de camarão-rosa Farfantepenaeus brasiliensis

Abstract: RESUMO Os experimentos foram realizados para investigar os efeitos da amônia, nitrito e nitrato no consumo alimentar de juvenis de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…Nitrite is a common toxic substance in culture systems, and the stress may affect hemocyanin synthesis and energy metabolism, resulting in the prawn's death (Li et al 2019). Moreover, even if they do not cause mortality, they can directly affect growth and food consumption (Tomasso 1994, Campos et al 2013, Maicá et al 2018.…”
Section: _________________mentioning
confidence: 99%
See 3 more Smart Citations
“…Nitrite is a common toxic substance in culture systems, and the stress may affect hemocyanin synthesis and energy metabolism, resulting in the prawn's death (Li et al 2019). Moreover, even if they do not cause mortality, they can directly affect growth and food consumption (Tomasso 1994, Campos et al 2013, Maicá et al 2018.…”
Section: _________________mentioning
confidence: 99%
“…Knowledge about food consumption is fundamental for food management to avoid excessive administration, which compromises water quality and insufficient supply of food that affects growth (Soares et al 2005). Although studies have shown that food consumption varies according to the weight of prawns, different results among species and experimental conditions have been described (González-Peña et al 2002, Campos et al 2013, Maicá et al 2018.…”
Section: _________________mentioning
confidence: 99%
See 2 more Smart Citations
“…Particularly, high nitrite concentrations seem to be one of the general problems in biofloc culture facilities. The toxic effects of this compound to shrimp are related to a number of different species, causing effects in metabolism, oxygen and food consumption and, immune function (Liao et al, 2012;Campos et al, 2013Campos et al, , 2014Jiang et al, 2014). In biofloc culture systems, high concentrations of nitrite were reported in many studies (Cohen et al, 2005;Vinatea et al, 2010), and until now, few effective techniques to deal with this problem were found.…”
Section: Introductionmentioning
confidence: 99%